Observers or activists? Citizen journalists and the public sphere - Kuś, Michał (Political Preferences, 2017)
Citizen journalism is frequently perceived as one of the most important developments in the media in early XXI century. However, several important issues have to be discussed in order to describe the nature of this phenomenon. One of these questions refers to the way citizen journalists cover important social and political events and debates – trying to participate in the public debate, and to shape public sphere. The most important question in this respect is: are they mostly neutral observers – or rather engaged activists? On the other hand, independently from the answer regarding mentioned question, we need to assess citizen journalists’ ability to product newsworthy, relevant stories which at the same time meet the standards of “serious” journalism (with its basic rules, as separation of facts and opinion). All these issues are analyzed in this article in context of results of research project “Training or improvisation? Citizen journalist and their journalistic education”, carried out in six European countries (United Kingdom, Germany, Austria, Switzerland, Italy, and Poland). This text concentrates on results from Poland, providing also some comparative data from other five countries. Research methods included: desk study which helped to map the field of citizen journalism and provide the most relevant examples in each country as well as semi-structured interviews with 9 (in each country, 54 in sum) practitioners in the field, representing three different types of citizen journalism. Key words: citizen journalism, participatory journalism, public sphere, activism, journalistic ethics, digital media